Cryo‐EM reveals the complex architecture of dynactin's shoulder region and pointed end - Lau, Clinton K; O’Reilly, Francis J; Santhanam, Balaji; Lacey, Samuel E; Rappsilber, Juri; Carter, Andrew P (The EMBO journal, 2021)
Dynactin is a 1.1 MDa complex that activates the molecular motor dynein for ultra‐processive transport along microtubules. In order to do this, it forms a tripartite complex with dynein and a coiled‐coil adaptor. Dynactin consists of an actin‐related filament whose length is defined by its flexible shoulder domain. Despite previous cryo‐EM structures, the molecular architecture of the shoulder and pointed end of the filament is still poorly understood due to the lack of high‐resolution information in these regions. Here we combine multiple cryo‐EM datasets and define precise masking strategies for particle signal subtraction and 3D classification. This overcomes domain flexibility and results in high‐resolution maps into which we can build the shoulder and pointed end. The unique architecture of the shoulder securely houses the p150 subunit and positions the four identical p50 subunits in different conformations to bind dynactin’s filament. The pointed end map allows us to build the first structure of p62 and reveals the molecular basis for cargo adaptor binding to different sites at the pointed end. Synopsis Cryo‐electron microscopy structures of dynactin’s shoulder and pointed end show the complex architecture of the shoulder domain and reveal how different adaptors bind to conserved sites on the pointed end. Combination of different dynactin cryo‐EM datasets and signal subtraction with optimized masks produce sidechain resolution structures of dynactin’s domains. The shoulder’s unique architecture leads to the anchoring of the p150 projection and the asymmetric presentation of the four p50 subunits. The pointed end structure reveals the conserved residues that interact with dynein’s cargo adaptors. Graphical Abstract Refinement of dynactin cryo‐EM structures offers insights into dynactin subunit organization in the shoulder region and adaptor binding to its pointed end.